Modelling a virtual urban environment with realistic terrain features - Maria Dolores Robles Ortega (2009)
Most of the urban models nowadays consider towns as a flat area without sloping zones. However, in order to obtain a realistic model of a city we need to include the information provided by its Digital Elevation Model (DEM). A global representation using the surface topography and the information usually given by an urban GIS (the geometry of buildings, blocks and streets and additional data about street names, number of floors in buildings, etc.) could provide realistic 3D models of urban environments. Nevertheless we find many non-solved problems to deal with, which we address in this paper and provide some research directions.